The effect of ginkgo biloba extract in experimental strangulation ileus in a rat model - Adnan ŞAHİN; Ömer ÇOLAK; Özkan ALATAŞ; Cengiz BAYÇU; H. Ahmet KASAP; Bekir YAŞAR; Ertuğrul KARAHÜSEYİNOĞLU; Haluk KİPER (Turkish Journal of Gastroenterology, 2020)
-